Tindakan Tenaga Kesehatan dalam Menerapkan Protokol Kesehatan Saat Berangkat Kerja pada Era Kebiasaan Baru - Fajar Akbar; Fahrul Islam; Agus Erwin Ashari; Abbas Mahmud; Ashriady Ashriady; Rahmat Haji Saeni (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Health workers have been the spearhead of the government in handling Covid-19 cases. Therefore, they need to get special attention so that their health is maintained while handling Covid-19 patients. The purpose of this study was to determine the actions of officers in implementing health protocols when leaving for work in a new normal era. This research method is an observational study with an accidental sampling of 163 health workers who work in health facilities in the Mamuju district. The results showed that the health workers applied health protocols when leaving for work were high, starting from using masks, carrying hand sanitizers, carrying spare masks, staying at home if there were complaints of colds and fever, maintaining distance when using public transportation, driving using private helmet, and always use hand sanitizer after handling money. Meanwhile, the low action is paying in non-cash when using public transportation. The conclusion in this study is that in general, the actions of health workers in implementing health protocols when leaving for work were high.